Dynamic neutron diffraction study of thermal stability and self-recovery in aluminium titanate - Low, It-Meng; Oo, Zeya (American Ceramic Society, 2010)
Aluminium titanate (Al2TiO5) is an excellent refractory and thermal shock resistant material dueto its relatively low thermal expansion coefficient and high melting point. However, Al2TiO5 unstableand undergoes a eutectoid-like decomposition to a-Al2O3 and TiO2 (rutile) at the temperature range of900-1280C. In this paper, we describe the use of high-temperature neutron diffraction to study (a) thephenomenon of self-recovery in decomposed Al2TiO5, and (b) the role of grain size on the rate ofisothermal decomposition at 1100C. It is shown that the process of decomposition in Al2TiO5 isreversible whereby self-recovery occurs readily when decomposed Al2TiO5 is re-heated above 1300C,and the rate of phase decomposition increases as the grain size decreases.